Application of light sheet microscopy for qualitative and quantitative analysis of bronchus-associated lymphoid tissue in mice. Issue 10 (October 2018) - Mzinza, David; Fleige, Henrike; Laarmann, Kristin; Willenzon, Stefanie; Ristenpart, Jasmin; Spanier, Julia; Sutter, Gerd; Kalinke, Ulrich; Valentin-Weigand, Peter; Förster, Reinhold
Abstract Bronchus-associated lymphoid tissue (BALT) develops at unpredictable locations around lung bronchi following pulmonary inflammation. The formation and composition of BALT have primarily been investigated by immunohistology that, due to the size of the invested organ, is usually restricted to a limited number of histological sections. To assess the entire BALT of the lung, other approaches are urgently needed. Here, we introduce a novel light sheet microscopy-based approach for assessing lymphoid tissue in the lung. Using antibody staining of whole lung lobes and optical clearing by organic solvents, we present a method that allows in-depth visualization of the entire bronchial tree, the lymphatic vasculature and the immune cell composition of the induced BALT. Furthermore, three-dimensional analysis of the entire lung allows the qualitative and quantitative enumeration of the induced BALT. Using this approach, we show that a single intranasal application of the replication-deficient poxvirus MVA induces BALT that constitutes up to 8% of the entire lung volume in mice deficient in CCR7, in contrast to wild type mice (WT). Furthermore, BALT induced by heat-inactivatedE. coli is dominated by a pronounced T cell infiltration inCxcr5- deficient mice, in contrast to WT mice.